PENGARUH DESAIN PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN KAOS DISTRO HEURAS GENGGERONG - Abdul Fatah; Dhiya Ulhaq Jundullah; Julia Valdah Ariany Abdillah; Jijah Hilyatul Ajijah (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
Heuras Genggerong distro is a creative industry in the fashion sector. The tighter competition between the existing distributions in Karawang has made the Heuras Genggerong distro face serious challenges from its competitors, because of the similarities in the products offered. This study aims to determine the effect of product design and lifestyle on purchasing decisions for Heuras Genggerong Distro t-shirts. In this study the authors used descriptive and verification methods with incidental sampling techniques to 100 respondents. The types of data collection through questionnaires, interviews, observation, and literature study. Qualitative and quantitative are analytical techniques used by the author. It is known that the results of statistical analysis of product design and lifestyle have a positive and significant effect on purchasing decisions. Between product design and lifestyle, the effect simultaneously on purchasing decisions is 73.7% and for 26.3% it is influenced by other variables. It can be concluded from these results that product design and lifestyle have an influence on purchasing decisions partially or simultaneously.